Aerospace series. Steel FE-PM1507 (X1CrNiMoAlTi12-11-2). Vacuum induction melted and consumable electrode remelted. Solution treated and precipitation treated. Bars. a or D ≤ 200 mm. Rm ≥ 1650 MPa. (31st October 2011) - British Standards Institution,
No abstract available